Livestock Rearing Practices in Arid Fringes of Rajasthan - Rohilla, P P; Chand, Khem; Mathur, D C (Annals of Arid Zone, 2016)
A survey on livestock rearing practices in Pali district of Rajasthan was conducted during January to December, 2002. The liv stock maintained by farmers are local/non-descript types except a few. A significant increase in buffalo population in last five years indicated of its vital role in improving dairy farmers’ economy in arid region also. The nutritional status of the livestock was not satisfactory due to scarcity of feed/fodder in the drought year. M iority of the livestock owners were ignorant about balanced feeding. No elaborate housing was provided to animals in rural areas, except a temporary protection during winter months. Livestock owners were not much concerned about animal health, especially cattle, which they consider uneconomical. Proper marketing facilities for animal products like goat and camel milk, meat and wool lacking.